Analisa Kepuasan Pelanggan Pengangkutan Sampah Menggunakan Metode Importance Performance Analysis (Studi Kasus Pada Dinas Lingkungan Hidup Kabupaten Jember) - Harvian Bagus Dewantara; Hary Sulaksono (Program Studi Manajemen, Sekolah Tinggi Ilmu Ekonomi Mandala, 2022)
This study aims to determine what quality dimension attributes have met customer satisfaction for waste transportation of the Department of the Environment of Jember Regency. The data used in this study are primary data. The data processing method in this study uses the Data Instrument Test Analysis method, namely: Validity Test and Reliability Test, and uses the Importance Performance Analysis (IPA) analysis method, using 5 service quality dimension attributes, namely Physical Evidence (Tangibles), Reliability (Reliability), Responsiveness, Assurance, and Empathy (Emphaty). The results showed that the Reliability Dimension has a very low gap value, which indicates that the quality of service provided by the Environmental Service Office of Jember Regency is very satisfying for customers. Meanwhile, the dimension of responsiveness has the highest gap, which can be concluded that there is dissatisfaction for customers with the responsiveness of the Jember Regency Environmental Service in dealing with existing problems. This of course will become a reference for the Jember Regency Environmental Service in improving the quality of its services.